The sorption of Tebuconazole and Linuron from an Aqueous Environment with a Modified Sludge-Based Biochar: Effect, Mechanisms, and Its Persistent Free Radicals Study - Jingjie Yang; Hongwei Sun; Yucan Liu; Xiaohan Wang; Kamran Valizadeh (Journal of Chemistry)
In this study, the sludge-based biochar was prepared and utilized as an adsorbent for the removal of two commonly used pesticides in agriculture, namely tebuconazole (Teb) and linuron (Lin) in an aqueous solution. The main contributing factors such as biochar preparation conditions, persistent free radicals as well as contact time, agitation speed, biochar dose, temperature, and pH were investigated. The physicochemical properties were characterized by SEM + EDS, FTIR, BET, EPR, etc. The results showed that the maximum adsorption capacities based on the Langmuir model was 7.8650 mg g−1 for tebuconazole and that based on Freundlich model was 9.0645 mg·g-1 for linuron at 25°C. The pseudo-second-order kinetic equations were all fitted well to the kinetic process of the adsorption of the two pesticides with all R2 ≥ 0.915. The maximum values of tebuconazole adsorption capacity occur at pH = 3. Meanwhile, linuron was not affected by pH. Both Cr6+ (r = −0.793∗∗/ −0.943∗∗) and humic acid (r = −0.798∗∗/ −0.947∗∗) significantly inhibited the adsorption amount of tebuconazole and linuron onto the biochar. Electron spin resonance signals (ESR) indicated that environmentally persistent radicals (EPFRs) are preferentially formed at lower pyrolysis temperatures and lower transition metal concentrations. The g-factors for BC400, BC600, BCF400, and BCF600 were 2.0036, 2.0035, 2.0034, and 2.0033, respectively, indicating that the EPFRs mainly have a carbon-centered structure with adjacent oxygen atoms. In addition, to close to the actual situation, natural water (from YanTai) was collected to simulate pesticide contamination. This study demonstrates that sludge-based biochar can achieve efficient removal of tebuconazole and linuron in aqueous environment in a short period of time with no secondary environmental risk especially on the waste activated sludge.